2020
DOI: 10.1177/1591019920936923
|View full text |Cite
|
Sign up to set email alerts
|

Cangrelor dose titration using platelet function testing during cerebrovascular stent placement

Abstract: Background Optimal antiplatelet inhibition is vital during cerebrovascular stenting procedures, yet no standardized recommendation exists for antithrombotic therapy in these scenarios. Cangrelor is an intravenous P2Y12 inhibitor with a favorable pharmacokinetic profile for use during neuroendovascular stenting. Methods A retrospective review of all neuroendovascular patients who underwent stenting between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…When half the cardiac dose was used, similar to our study, all seven patients with acute ischemic stroke had adequate (PRU < 200) antiplatelet activity and no evidence of intracranial hemorrhage or in-stent thrombosis (29). Lastly, a study by Entezami et al treated 21 patients with ischemic stroke or symptomatic critical stenosis (32). A cangrelor bolus of 5 mcg/kg was followed by a maintenance infusion of 0.75 or 1 mcg/kg/min.…”
Section: Discussionsupporting
confidence: 68%
“…When half the cardiac dose was used, similar to our study, all seven patients with acute ischemic stroke had adequate (PRU < 200) antiplatelet activity and no evidence of intracranial hemorrhage or in-stent thrombosis (29). Lastly, a study by Entezami et al treated 21 patients with ischemic stroke or symptomatic critical stenosis (32). A cangrelor bolus of 5 mcg/kg was followed by a maintenance infusion of 0.75 or 1 mcg/kg/min.…”
Section: Discussionsupporting
confidence: 68%
“…17,18 More recently, efforts have been invested into defining a therapeutic window for cangrelor within the interventional cardiology and neuroendovascular literature, with no current consensus. 19 Studies have shown an increased risk of bleeding with PRUs of less than 50 to 80 and an increased risk of thrombosis at PRUs approaching 200. 10 Thus, our institution initially derived our PRU range of 50 to 194 as being optimal, to balance risk of bleeding and ischemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…74 Of course, caution in patients with intraventricular drains or those in need of surgical intervention is the rule, 75,76 it should be noted that there exists a patient population which receives anti-platelet drugs following coil embolization with minimal complications. 7780 So why are anti-platelets not more widely used for aSAH patients? Despite their safety in use, trials of anti-platelet agents have not shown a clear clinical benefit.…”
Section: Platelets As a Therapeutic Target To Prevent DCImentioning
confidence: 99%
“…Several platelet activation receptors (protease activated receptors (PAR), thromboxane receptors, purinergic receptors (P2Y)) have been tested as therapeutic targets for aSAH. 74,78,9195 Two activation receptors which may be promising are the GPIb-IX-V complex and GPVI. The GPIb-IX-V complex interacts with vWF and thrombin, and is crucial in platelet adhesion to endothelial cells and stabilizing microclots.…”
Section: Alternative Anti-platelet Targetsmentioning
confidence: 99%